Pengaruh Brand Ambassador dan Word of Mouth Terhadap Brand Awareness Produk Ms. Glow di Kota Singaraja - Luh Pani Atmini; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This research was conducted to examine: (1) the effect of Brand Ambassador on Brand Awareness of Ms Glow's products, (2) the effect of Word of Mouth on Brand Awareness of Ms Glow's products, and (3) the influence of Brand Ambassador and Word of Mouth on Brand Awareness of Ms Glow's products. This type of research is causalitative research. The population in this study were all consumers of Ms Glow in the city of Singaraja. The population in this study is unknown because there is no exact data regarding the number of Ms Glow consumers in Singaraja City and the total sample is 110. The sample technique used is purposive sampling technique. Methods of data collection using a questionnaire with the method of data analysis, namely multiple linear regression analysis. The hypothesis test uses the t test and F test which are processed with the help of SPSS 25 for windows. The results of this study indicate that: (1) brand ambassadors have a positive and significant effect on brand awareness of Ms Glow products with a significance value of 0.000 <0.05, (2) word of mouth has a positive and significant effect on brand awareness of Ms Glow products with a significance value of 0.000 <0.05, and (3) brand ambassadors and word of mouth have a positive and significant effect on brand awareness of Ms Glow's products with a significance value of 0.000 <0.05.